Performance and bone integrity of broilers in response to dietary supplementation with four sources of commercial phytases - Aguilar V., José (2018)
The aim of this study was to determine the effects of four sources of commercial phytases on the performance and bone integrity of broilers from 1 to 28 days of age. Three hundred 1-day old Cobb 500 male chickens were distributed in 30 pens (10 birds per pen) and fed with the experimental diets for 28 days. The treatments were: T1, diet with adequate phosphorus (PAD); T2, phosphorus deficient diet (PDD); T3, PDD + phytase A (100 g/t); T4, PDD + phytase B (100 g/t); T5, PDD + phytase C (50 g/t) and T6, PDD + phytase D (50 g/t). Feeds and water were provided ad libitum. Body weight, body weight gain, feed consumption, feed conversion, and mortality were recorded weekly. At 28 days of age, 20 chicks per treatment were slaughtered to determine carcass and leg yield and tibia weight, plus bone moisture and ash content in the tibia. The results showed that the productive performance of broilers fed diets with normal levels of phosphorus (T1) were significantly higher (p<0.05) than chicks in the other treatments. Similarly, treatments T3 and T5 and treatments T4 and T6 presented similar responses, while T2 (deficient level of phosphorus) showed lower yields. Bone ash in all treatments, except for T2 (p<0.05), showed adequate levels. It was concluded that the productive responses of the birds that received diets deficient in phosphorus with the addition of phytase were lower than the level of response of the birds fed the diet with adequate level of phosphorus.